Hubungan Jumlah Kadar Limfosit dan Neutrofil Segmen Pada Apendisitis Akut - Mizar Erianto; Zulhafis Mandala; Rio Chairul Anam (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Appendicitis is one of the most common cases in the field of abdominal surgery which causes acute abdominal pain and requires immediate surgery to prevent complications that are generally dangerous, such as gangrenous, perforation, and even generalized peritonitis. Appendicitis can be found in both men and women with a risk of suffering from appendicitis in their lifetime reaching 7-8%. The highest incidence is reported in the age range of 20 to 30 years. Methodology: The type of research used in this study is an observational analytic study with a cross-sectional study design using medical records as data. The population in this study were all patients with appendicitis recorded in medical records. The data were analyzed using the Spearman test. Results: In this study, 26 people with a percentage of 65% had abnormal lymphocyte counts. as many as 31 people with a percentage of 77.5% who had abnormal neutrophils. For the neutrophil variable with the incidence of appendicitis using the Spearman test, the p-value = 0.005 (p <0.05). In the lymphocyte variable with the incidence of appendicitis using the Spearman test, the p-value = 0.058 (p <0.05) was obtained. Conclusion: There is a significant relationship between neutrophil and appendicitis. Meanwhile, the lymphocyte variable with the incidence of appendicitis had no significant relationship.